2D Hybrid Nanostructured Dirac Materials for Broadband Transparent Electrodes. (16th June 2015) - Guo, Yunfan; Lin, Li; Zhao, Shuli; Deng, Bing; Chen, Hongliang; Ma, Bangjun; Wu, Jinxiong; Yin, Jianbo; Liu, Zhongfan; Peng, Hailin
<x xml:space="preserve">Abstract</x> Broadband transparent electrodes based on 2D hybrid nanostructured Dirac materials between Bi2Se3 and graphene are synthesized using a chemical vapor deposition (CVD) method. Bi2Se3 nanoplates are preferentially grown along graphene grain boundaries as "smart" conductive patches to bridge the graphene boundary. These hybrid films increase by one‐ to threefold in conductivity while remaining highly transparent over broadband wavelength. They also display outstanding chemical stability and mechanical flexibility.